IDENTIFIKASI KERAGAMAN GENETIK KENTANG SUPEJOHN TRANSGENIK (Solanum tuberosum L. var supejohn) - Lengkong, Christine L.W.; Polii-Mandang, Jeany; Lengkong, Edy F. (EUGENIA, 2012)
ABSTRACT   The aim of this study was to determine the genetic diversity of potato Supejohn transgenic that had been twenty-five times subcultured with exploration  method. The genetic variability was calculated using molecular marker Polimorphic Random Amplified DNA (RAPD) analysis of ten samples from four weeks planlets of Supejohn transgenic plants using ten random primers. DNA isolation of 10 samples using CTAB buffer  then measurement of the DNA qualification and quantification,  afterwards amplification of DNA by PCR using 10 random primers followed by electrophoresis on a 1% agarose gel with TAE 1x electrode buffer solution. Visualisation  the results used UV Transluminator to see DNA bands and the data of  polymorphic bands had been analized used the NTSYS-pc version of 1.07 program to obtain the similarity coefficient  and the dendrogram.The results showed that five random primers produced polymorphic DNA bands with 0.39 - 0.88 similarity coefficient  and the average similarity coefficient is 0.63 (63%) or the genetic diversity of the samples as many as 37%. Dendrogram formed eight distinct clusters corresponding similarity coefficient, the formation of clusters means that there is genetic diversity among the DNA samples. Keywords: potato Supejohn transgenic, RAPD, genetic diversity ABSTRAK Penelitian ini bertujuan untuk  menentukan keragaman genetik kentang Supejohn transgenik yang telah dua puluh lima kali disubkultur dengan menggunakan metode penelitian eksplorasi dengan penanda molekuler  Random Amplified Polimorphic DNA (RAPD) terhadap 10 sampel tanaman Supejohn transgenik, berumur empat minggu dan  menggunakan  10 primer random.  Isolasi DNA dari 10 sampel menggunakan buffer CTAB sesudah itu dilakukan pengukuran kualitas dan kuantitas  DNA, kemudian dilanjutkan dengan amplifikasi DNA secara PCR menggunakan 10 primer random diikuti dengan  elektroforesis pada gel agarose 1% dengan larutan penyanggah elektroda TAE 1x. Visualisasi hasil elektroforesis  menggunakan UV Transluminator untuk melihat pita DNA  dan analisis  data pita polimorfik  menggunakan program NTSYS-pc versi 1.07 sehingga didapatkan koefisien kesamaan dan dendrogram. Hasil penelitian menunjukkan bahwa lima primer random menghasilkan pita DNA polimorfik dengan koefisien kesamaan 0.39 – 0.88 dan rata-rata koefisien kesamaan yaitu 0.63 (63%) atau  keragaman  genetik sampel sebesar 37%.  Dendrogram  membentuk delapan cluster yang berbeda sesuai koefisien kesamaan,terbentuknya clusters mengartikan bahwa ada keragaman genetik antar sampel DNA. Eugenia Volume 18 No. 3  Desember 2012 Kata kunci : kentang Supejohn transgenik , RAPD, keragaman genetik